Acantholytic Anaplastic Extramammary Paget's Disease: A Case Report and Review of the Literature - Oh, Yu-Jin (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2011)
Extramammary Paget's disease (EMPD) is an uncommon intraepithelial neoplasm that most commonly arises on the vulva and perianal region. Very few cases of EMPD revealing a histological Bowenoid appearance have been reported. This study describes scrotal EMPD presenting with histological features of Bowen's disease in a 79-year-old man. He presented with a 5-year history of a pruritic erythematous plaque and a verrucous papule on the scrotum. The verrucous papule histopathologically showed Bowenoid features, and the erythematous plaque demonstrated acantholytic EMPD. Immunohistochemical findings revealed strong expression for carcinoembryonic antigen, Cam 5.2, epithelial membrane antigen, cytokeratin (CK) 7, and pancytokeratin (AE1/AE3) in both areas, but negative CK20 staining, supporting the overall diagnosis of primary acantholytic anaplastic EMPD. This is the first reported case of acantholytic anaplastic EMPD in the Korean literature.